2021
DOI: 10.1111/azo.12409
|View full text |Cite
|
Sign up to set email alerts
|

Hidden taxonomic characters in otoliths of blenniid fishes (Teleostei: Blenniidae) from the Iranian coasts of the Persian Gulf and Oman Sea ecoregions: A scanning electron microscopy approach

Abstract: In the present work, the morphological characteristics of sagitta were described and analysed for 10 species of combtooth blennies (Blenniidae) inhabiting the intertidal region of the Persian Gulf and Makran zone of Oman Sea to see the taxonomic usefulness of otoliths, especially their hidden characters for species identification. Based on the obtained results, sagitta morphology could be considered as diagnostic characters distinguishing the genera Alticus, Antennablennius, Istiblennius, Omobranchus and Parab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…The diagnostic features of the otoliths obtained in the present study can be added to the specific characters of every species. Comparable results were obtained by Reichenbacher et al (2007), Echreshavi et al (2021), andMehraban et al (2021) on fish species other than lethrinids. Additional research is essential, including a comparative study of the shape and geometry of the sagittal otolith, to contribute further taxonomic characters for the recognition of these species.…”
Section: Discussionsupporting
confidence: 69%
“…The diagnostic features of the otoliths obtained in the present study can be added to the specific characters of every species. Comparable results were obtained by Reichenbacher et al (2007), Echreshavi et al (2021), andMehraban et al (2021) on fish species other than lethrinids. Additional research is essential, including a comparative study of the shape and geometry of the sagittal otolith, to contribute further taxonomic characters for the recognition of these species.…”
Section: Discussionsupporting
confidence: 69%
“…Analysis of the shapes of otoliths has significantly contributed to knowledge of teleost systematics and biodiversity [2][3][4][5][6][7], as well as historic diversity, phylogeny, zoogeography, and climatology [8][9][10][11][12], ancient and modern fisheries [13], life history and habitat [14], and population structure [6,7,15]. The sagittal otolith (referred to as otolith hereforth) is of particular interest, since it often possesses distinctive morphological features that vary among populations, species, and genera [10,[16][17][18]. Some studies have concluded that otolith shape is primarily defined by genetic factors [19][20][21], however, others suggest that while genetics constrain the overall otolith's shape, environmental conditions often alter its somatic growth rates, which can affect the otolith's shape and result in intraspecific variation across the species' distribution [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Otoliths display numerous shapes in different species and populations, and thus they can show a species-specific morphology. Although three types of otoliths exist on each side of the teleost fish head, most of the investigations and analyses are being carried out on the biggest one (in many teleost fishes), which is called sagitta or saccular otolith (Echreshavi et al, 2021;Mehraban et al, 2021). These analyses are valuable in age and growth studies (Campana & Neilson, 1985;Green et al, 2009), migration, and realizing larval phases (Avigliano et al, 2014;Lord et al, 2010), as well as paleobiologic and systematic studies on fishes (Echreshavi et al, 2021;Gierl et al, 2013;Lord et al, 2012;Mehraban et al, 2021;Nolf, 1985Nolf, , 2013Tuset et al, 2008Tuset et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Although three types of otoliths exist on each side of the teleost fish head, most of the investigations and analyses are being carried out on the biggest one (in many teleost fishes), which is called sagitta or saccular otolith (Echreshavi et al, 2021;Mehraban et al, 2021). These analyses are valuable in age and growth studies (Campana & Neilson, 1985;Green et al, 2009), migration, and realizing larval phases (Avigliano et al, 2014;Lord et al, 2010), as well as paleobiologic and systematic studies on fishes (Echreshavi et al, 2021;Gierl et al, 2013;Lord et al, 2012;Mehraban et al, 2021;Nolf, 1985Nolf, , 2013Tuset et al, 2008Tuset et al, , 2012. In addition, it provides important information about habitat conditions and has a significant role in the auditory system and balance (Campana & Thorrold, 2001;Lombarte & Lleonart, 1993;Schulz-Mirbach et al, 2011).…”
Section: Introductionmentioning
confidence: 99%